2007
DOI: 10.1103/physrevb.75.165317
|View full text |Cite
|
Sign up to set email alerts
|

Thin films of oxygen-deficient perovskite phases by pulsed-laser ablation of strontium titanate

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 26 publications
8
64
1
1
Order By: Relevance
“…The epitaxial growth was confirmed by X-ray diffraction. This film showed a metallic behaviour down to 10 K coming from oxygen vacancy induced mobile electrons in the system as reported earlier by Perez-Casero et al 29 To grow the amorphous film, the deposition was carried out at room temperature under 1 × 10 −4 mbar of oxygen. Two samples of each type were prepared.…”
Section: Resultssupporting
confidence: 58%
“…The epitaxial growth was confirmed by X-ray diffraction. This film showed a metallic behaviour down to 10 K coming from oxygen vacancy induced mobile electrons in the system as reported earlier by Perez-Casero et al 29 To grow the amorphous film, the deposition was carried out at room temperature under 1 × 10 −4 mbar of oxygen. Two samples of each type were prepared.…”
Section: Resultssupporting
confidence: 58%
“…[38,39] Therefore, the oxygen-vacancy-induced 2D conduction is more localized in STO-filmbased 2DEG-V and that is also why the oxygen-vacancy-induced 3D conduction shows the low-temperature semiconducting phase in oxygen-deficient STO films. [17][18][19][20] Now looking back into the growth-temperature-dependent bandgap in Figure 3, we can draw a conclusion that a high growth temperature is useful to suppress point defect such as Sr/Ti defects. For example, the STO single crystal growth temperature is more than 1500 °C, which helps to minimize point defects.…”
Section: The Composition Of the Pld-grown Crystalline Sto (C-sto) Filmentioning
confidence: 99%
“…Instead, oxygen-deficient STO films are typically semiconducting at low temperatures. [17][18][19][20] Besides, the 2DEG at the LAO/STO interface fabricated on STO films [21][22][23][24] is more localized at low temperatures than that fabricated on STO single crystals; [7] it was found that the insertion of a STO film layer degrades the LAO/STO interface significantly; [25,26] the fully metallic state of the LAO/STO interface based on STO films is achieved when STO films are deposited at a very high temperature of 1100 °C. [27] These perhaps indicate the presence of point defects/disorder in the STO films deposited at the typical temperature range of 600-800 °C.…”
mentioning
confidence: 99%
“…Pulsed laser deposition of oxides in a high vacuum typically results in the formation of oxygen-deficient films [33,34], because the light oxygen species (atoms and ions) have a lower sticking probability and a higher scattering degree in the ablation plasma plume, compared to the heavier cationic species. Thus, deposition of oxide films by PLD requires an additional source(s) of O to achieve deposition of films without oxygen deficiencies.…”
Section: General Aspects Of Film Depositionmentioning
confidence: 99%
“…The most commonly used sources of O are the background gas [20,34], a gas pulse (PRCLA) [26,29], and a RF-induced plasma plume (RFplasma assisted PLD) [35]. In our experiments the growing strontium titanate films are expected to contain anionic vacancies as no additional sources of O are used [33]. In the presence of reactive nitrogen species in the plasma these vacancies can be occupied by N atoms resulting in the formation of an oxynitride phase.…”
Section: General Aspects Of Film Depositionmentioning
confidence: 99%